Anissa Helou: Mediterranean Street Food - Jaine, Tom (Petits Propos Culinaires, 2024)
Anissa Helou: Mediterranean Street Food: HarperCollins, New York, 2002: ISBN 0060195967: 278 pp., sepia photos by the author, h/b, $29.95.